Islamic Workplace Spirituality and Its Influence on Employee Well-Being and Performance: A Systematic Literature Review - Sobana, Dadang Husen; Hakiki, Muhamad Fuji; Arshad, Noraziah Che (Universitas Muhammadiyah Yogyakarta, 2026)
This study aims to explore Islamic Workplace Spirituality (IWS) as a conceptual framework for assessing employee well-being and organizational performance. The search process follows a systematic literature review based on the PRISMA protocol. The review examines Scopus-indexed journal articles on Islamic workplace spirituality, employee well-being, and performance published between 1998 and 2025. A systematic search using predetermined keywords was conducted in the Scopus database, and the selection process followed the PRISMA stages of identification, screening, eligibility, and inclusion. From an initial total of 4,568 documents, twenty-one articles met the inclusion criteria and were thoroughly analyzed as shown in Table 1. The results conclude that Islamic Workplace Spirituality positively correlates with employee psychological comfort, meaningful work, ethical behavior, and inner peace. The review further demonstrates that work-related outcomes, measured in the context of workplace spirituality, include not only task-oriented behaviors but also moral responsibility, voluntary helping behavior, and commitment to organizational values. In addition, the analysis brings together and integrates key measurement indicators into an integrated framework rooted in Islamic epistemology (especially classical wisdom influenced by Al-Ghazali). This paper adds to the literature by showing that spiritual dimensions can be an integral part of organizational evaluation frameworks and by offering measurement indicators for future empirical research. This study is innovative because it has contributed to integrating Islamic workplace spirituality with employee well-being and performance through a holistic, systematic review.